The Voice of the Ulema and Dilemma of the Indonesian Ulema Council’s Fatwa among Low Literate Society - Fariz Alnizar; Achmad Munjid (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2020)
Some Islamic movements in Indonesia, which make the fatwas issued by the Indonesian Ulema Council (MUI) a reference for their actions, recently found their momentum after the defense movements called 411 and 212. The proponents of these movements are called Gerakan Nasional Pengawal Fatwa Majelis Ulama Indonesia (GNPF-MUI), which means The National Movement of the Guardians of the Indonesian Ulema Council’s Fatwa. By the employment of a qualitative approach coupled with a historical-causal paradigm, this article examines the main question, which asks if the proponents of these movements substantially understand the fatwas they defend. The results of the research showed that the fatwas held a dilemmatic position. While some movements have insisted on making them a “sacred opinion” that must be protected and guarded, people do not substantially comprehend the fatwas they defend. This problem is caused by the cultural basis of the Indonesian society, which put more preference on orality than literality or, explicitly, written tradition.